Resource-use efficiency and environmental sustainability in the village tank cascade systems in the dry zone of Sri Lanka: An assessment using a bio-economic model - Dayananda, Dasuni; Weerahewa, Jeevika; Weerasooriya, Senal A. (Frontiers in Sustainable Food Systems, 2023)
Village Tank Cascade Systems (VTCSs) were built in ancient Sri Lanka as autonomous and climate-resilient agro-ecological systems. This study examined crop choices, farming profitability, and environmental sustainability under alternative rainfall regimes in Mahakanumulla VTCS in the Anuradhapura district. A bio-economic model was developed to represent farming activities in the VTCS for the 2018-19 Maha and 2019 Yala seasons using data gathered from secondary sources and a critical informant survey. The baseline equilibrium was calibrated by treating farmers as profit cultivating four types of land (uplands and lowlands in Maha and Yala seasons), using two types of labour (hired and family), and twelve-monthly water constraints. Six different models were developed by treating six sub-divisions of VTCS as different agricultural systems considering the water management hierarchy of the VTCS. The models were simulated under alternative rainfall regimes, market, and technological interventions. The optimal crop mixes, farm profits, and shadow prices of resources associated with the baseline scenarios were compared with those of counterfactual scenarios. The analysis results clearly illustrated that water and labour are the key determinants of the system. VTCS has annual profitability of 111 million LKR under normal environmental conditions, cultivating the 922 ha of lowlands and 205 ha of uplands per annum. However, the profit results reflected that the drought has resulted in a drastic reduction of profit to the VTCS and avoided cultivations in the Maha season. Year around drought caused a 77% profit reduction compared to the baseline, which was 47% under the Maha drought. The introductions of the buyback arrangement of chilli and maize have maximized the profitability of the current cropping pattern and can restore profitability loss under extreme climate scenarios. Policy decisions towards climate adaptation and eco-system conservation would drive towards rehabilitating VTCSs in Sri Lanka.